The role of educational media and family communication in reducing school dropout: A legal and analytical perspective on awareness and support mechanisms - Abismail, Kacem (The International tax journal, 2025)
This study addresses the issue of school dropout at the primary level in Algeria, considering it one of the most critical challenges facing the education system. Its negative consequences extend to the cognitive, social, and economic development of both the child and society. The research begins with a central question: To what extent can educational media and family communication help reduce this phenomenon? After reviewing the current state of school dropout and its various structural causes—social, psychological, educational, and communicational—the study highlights the potential of both traditional and digital educational media as preventive tools. It emphasizes their role in raising family awareness, shifting negative attitudes toward schooling, and fostering a culture that supports education. The paper also explores the importance of family and institutional communication in supporting students' academic paths. These forms of communication are seen as vital components of early psychological and educational support systems. Through this analysis, the study concludes that a comprehensive national strategy is needed—one that integrates educational media and communication as essential elements of the educational process. Practical recommendations are proposed to help achieve this objective.